Cerámica en el camino: los materiales del río Loa (Norte Grande de Chile) y sus implicaciones tipológicas y conductuales para la comprensión de la vialidad y la expansión del Tawantinsuyo - Uribe Rodríguez, Mauricio; Cabello Baettig, Gloria (Revista Española de Antropología Americana, 2005)
From a typological and behavioral analysis of pottery coming from a Southern section of the Inka Trail (Loa River, Northern Chile), this paper presents some conclusions about the different occupation moments, functionality and settlement type of several sites identified in such area during two fieldwork years. They are posed as an approach to Inka road system and its role in Tawantinsuyo’s expansion over and conquest of Atacama Desert’s populations.